Fiscal policy and social welfare an analysis of alternative tax and transfer systems - Creedy, John 1949- (Elgar, 1996)
Drawing on original research, this volume concentrates on the modelling of tax structures and the implications for social welfare and income distribution. After reviewing various inequality and tax progressivity measures, as well as social welfare functions, the discussion moves systematically from a framework with fixed labour supplies to one in which labour supplies respond to the changes in the tax system. Attention is given to taxes in a multi-period context, including the treatment of pension schemes
Keywords: Belastingen; Belastingpolitiek; Impôt sur le revenu - Modèles mathématiques; Impôt; Incidence fiscale - Modèles mathématiques; Inkomensverdeling; Justice distributive - Modèles mathématiques; Modèles mathématiques; Paiements de transfert; Politique fiscale; Renta, Distribución de la - Modelos matemáticos; Revenu - Répartition; Transferencia de pagos - Modelos matemáticos; Wiskundige modellen; Mathematisches Modell; Steuer; Income distribution -- Mathematical models; Tax incidence -- Mathematical models; Taxation -- Mathematical models; Transfer payments -- Mathematical models; Gleichgewichtsmodell; Steuersystem; Einkommensverteilung